Propagación sonora del ruido vehicular en espacios urbanos abiertos - Vechiatti, Nilda Susana (2011)
In carrying out studies of acoustic impact or noise mapping, the methods that can be applied to calculate the noise level generated by the road traffic have many points in common but differ in some important aspects. Essentially, they share the concept of considering the total flow of vehicles along a given road as a linear sound source and subdivide it into individual sources that can be treated as point sources. The sound level LAeq in a particular position of reception is given by the sum of the individual contributions, considering the corresponding attenuation that applies to the sound propagating from point to point. The segmentation of the linear source is one of the aspect in which two of the most publicized methods of calculation differ. In this work the results of prediction by applying the ISO 9613 model and the Harmonoise model are compared and contrasted with field measurements.